Langkah Kecil-Dampak Besar: Walking Tour sebagai Kunci Pariwisata Berkelanjutan di Kampung Peneleh Surabaya - Nugroho, Setyo; Audina, Shafira Zulfa; Sulistyandari, Utari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: Small Steps-Big Impact: Walking Tour as Key to Sustainable Tourism in Kampung Peneleh Surabaya A way to preserve historical areas through tourism is by organizing walking tours. Recently, there has been a surge in walking tours offering experiences in spatial and architectural history for both domestic and international tourists. One example is the locally organized walking tours. However, studies focusing on tourist experiences during these walking tours, directly involving tourists as participants, are still limited. Identifying observation points along the walking tour route is crucial to determine which sites elicit positive or negative responses from participants. This article aims to explore tourists' spatial and architectural experiences and assess the contribution of walking tours to sustainable tourism. The research focuses on a case study in the historical village of Peneleh, Surabaya, where walking tours are conducted by a tourism awareness group (pokdarwis). The study employs a qualitative approach, utilizing observation and photo surveys, with six tourists serving as participants who joined other tourists on a walking tour package. The results show 154 photos representing four participant responses: liked photos (50.6%), disliked (10.4%), helpful during the tour (19.5%), and areas needing improvement (19.5%). Participants captured liked objects while also noting areas that require improvement. Additionally, walking tours offer broader access to various tourist sites that are not always open to the public. Those initiated by Pokdarwis can be sustainable tourism activities, continually innovating tour themes and offering new experiences for tourists.